Gender gaps from labor market shocks - Ria Ivandic; Anne Sophie Lassen (W.E. Upjohn Institute for Employment Research, 2023)
Job loss leads to persistent adverse labor market outcomes, but assessments of gender differences in labor market recovery are lacking. We utilize plant closures in Denmark to estimate gender gaps in labor market outcomes and document that women face an increased risk of unemployment and lose a larger share of their earnings in the two years following job displacement. When accounting for observable differences in human Capital across men and women, half of the gender gap in unemployment remains. In a standard decomposition framework, we document that child care imposes an important barrier to women's labor market recovery regardless of individual characteristics.
Keywords: J16; J24; J65; 330; gender gaps; child care; job loss